Cities and climate change mitigation: Economic opportunities and governance challenges in Asia. (May 2016) - Gouldson, Andy; Colenbrander, Sarah; Sudmant, Andrew; Papargyropoulou, Effie; Kerr, Niall; McAnulla, Faye; Hall, Stephen
Abstract: Cities are central to the fight against climate change, but the IPCC recently noted that many cities — and particularly those in the developing world — lack the institutional, financial and technical capacities needed to switch to low emission development paths. Based on detailed case studies of three Asian cities, this paper finds that the adoption of low emission development strategies (LEDS) at the urban level could be economically attractive. However, it also argues that without a coordinated multi-level, cross-sectoral governance framework these opportunities for low carbon urban development are likely to be left unexploited. As these governance conditions are frequently not in place, we argue that these case study cities, and cities in similar contexts, are likely to miss even the economically attractive low carbon development opportunities and become increasingly locked in to higher cost, higher carbon development paths. Due to their growing size and importance, we conclude that the presence or absence of governance arrangements that enable the adoption of low carbon development strategies in Asian cities will have global implications for climate change. Highlights: Cities are central to the fight against climate change but often lack the capacities to act. We offer a detailed analysis of the relationship between growth, energy and carbon emissions in three Asian cities. We find significant economically attractive opportunities that could be integrated into low emission development strategies. Coordinated multi-level, cross-sectoral governance frameworks are needed if cities are to exploit these opportunities. In the absence of such frameworks cities are likely to lock in to higher cost, higher carbon development paths.